HUMAN RESOURCE MANAGEMENT: ANALYSIS OF TEACHER RECRUITMENT STRATEGIES - Hanifah, Najmy; Rindaningsih, Ida (International Journal Multidisciplinary (IJMI), 2024)
This study delves into the recruitment strategies of teachers within the framework of human resource management. Utilizing the Systematic Literature Review (SLR) approach, the research involves a review and identification of journal literature following established procedures. Journal articles are sourced from Google Scholar and Publish or Perish. Data collection follows the Population, Intervention, Comparison, and Outcome (PICO) method. The research findings reveal variations in teacher recruitment strategies, highlighting the complexity of approaches used by various educational institutions. The implications of these findings can offer further insights for the development of effective policies and practices in teacher recruitment within the context of human resource management in the field of education